Nitrosative stress and redox-cycling agents synergize to cause mitochondrial dysfunction and cell death in endothelial cells() - Diers, Anne R. (Elsevier, 2013)
Nitric oxide production by the endothelium is required for normal vascular homeostasis; however, in conditions of oxidative stress, interactions of nitric oxide with reactive oxygen species (ROS) are thought to underlie endothelial dysfunction. Beyond canonical nitric oxide signaling pathways, nitric oxide production results in the post-translational modification of protein thiols, termed S-nitrosation. The potential interplay between S-nitrosation and ROS remains poorly understood and is the focus of the current study. The effects of the S-nitrosating agent S-nitrosocysteine (CysNO) in combination with redox-cycling agents was examined in bovine aortic endothelial cells (BAEC). CysNO significantly impairs mitochondrial function and depletes the NADH/NAD(+) pool; however, these changes do not result in cell death. When faced with the additional stressor of a redox-cycling agent used to generate ROS, further loss of NAD(+) occurs, and cellular ATP pools are depleted. Cellular S-nitrosothiols also accumulate, and cell death is triggered. These data demonstrate that CysNO sensitizes endothelial cells to redox-cycling agent-dependent mitochondrial dysfunction and cell death and identify attenuated degradation of S-nitrosothiols as one potential mechanism for the enhanced cytotoxicity.